"It is easier to destroy than to create": Feedback and response - Seligmann, Linda J. (1992)
In his article "Losing the Revolution: Anthropologists and the War in Peru," Orin Starn presents us with a strangely distorted explanation of why so many anthropologists who had worked in the high Andean regions of Peru during the 1960s and 1970s could not foreshadow the coming of a violent conflict, in the form of the Peruvian Communist Party-Sendero Luminoso, and the support it would receive in the countryside.